2022
DOI: 10.4102/sajhrm.v20i0.2013
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership influences on work engagement and turnover intention in an engineering organisation

Abstract: This study examined how transformational leadership (TFL) moderates the relationship between work engagement (WE) and perceptions of turnover intention (TI) in an engineering organisation. Research purpose:The study seeks to address the paucity of research on the moderating effect of TFL on the relationship WE and TI in the South African working environment and more specifically in the engineering organisation.Motivation for the study: The engineering sector is an important contributor to the DGP, but faces a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…As stated in the results, employees are more engaged when they have better working conditions. Unhealthy employment relationships have multiple effects, resulting in poorer performance and less engagement in work (Ntseke et al 2022). Shaheen, Bin, and Abdul (2017) opine that employment relationships focus on the level of involvement employees have with the organisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in the results, employees are more engaged when they have better working conditions. Unhealthy employment relationships have multiple effects, resulting in poorer performance and less engagement in work (Ntseke et al 2022). Shaheen, Bin, and Abdul (2017) opine that employment relationships focus on the level of involvement employees have with the organisation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of essential work resources enables employees to become engaged in their jobs, and similarly improves their work performance (Pieters et al 2019). Engaged employees invest their energy into their jobs and express themselves physically, cognitively, and emotionally (Ntseke, Mitonga-Monga, and Hoole 2022). When employees experience engagement, they experience power, dedication and acceptance in their job (Pieters et al 2019).…”
Section: Concepts Of Work Engagementmentioning
confidence: 99%
“…Transformational Leadership: one method of leading and focusing on motivating the team to exceed their own expectations which focuses on improving morale and increasing employee motivation. Transformational leadership also helps to inspire, motivate, and give direction to their teams (Dominguez-Soto et al, 2021;Ntseke et al, 2022). Essentially, transformational leaders not only drive change but also transform their followers into leaders.…”
Section: Definition Of Termsmentioning
confidence: 99%
“…Work engagement plays a significant influence in lowering employee TI in previous research (Cao & Chen, 2021;Memon et al, 2020;Pattnaik & Panda, 2020). Researchers found that workers' productivity increased in proportion to their level of interest in their jobs (Li, Mohamed, Mahomed, & Khan, 2022;Ntseke, Mitonga-Monga, & Hoole, 2022). Multiple empirical research have found that personnel who are more invested in their relevant jobs are less likely to leave them (Urrutia Pereira, de Lara Machado, & Ziebell de Oliveira, 2022; Winarno, Kisahwan, & Hermana, 2022).…”
Section: 67the Relationship Between We and Timentioning
confidence: 99%